Asynchronous Decentralized Event-Triggered Control for Switched Large-Scale Systems Subject to Data Congestions and Disorders - Qi, Yiwen; Xing, Ning; Zhao, Xudong; Guan, Wei; Yuan, Shuo; Cao, Zheng (IEEE systems journal, 2021)
In this article, the asynchronous sampling based decentralized event-triggered H_∞ control for switched large-scale systems with disturbance and network communication delay is studied. For each sub large-scale system, distributed sensors are adopted to sample at different rates on multiple channels and transmit measurements asynchronously. Specifically, an asynchronous sampling based decentralized event-triggering scheme (AS-DETS) is first developed. Then, data buffers are utilized to organize multiple released data from different channels to update controllers. With the AS-DETS and data buffers, the resulting closed-loop switched large-scale system is derived. In particular, for the problem of data congestions and disorders caused by asynchronous sampling and large transmission delay, a packet loss method is proposed to ensure the performance of the developed system. Moreover, by using piecewise Lyapunov functional and average dwell time method, sufficient conditions are constructed to guarantee the global exponential stability with an H_∞ performance of the closed-loop system. In view of the stagger between the event-triggered instants and the switching instants, their coupling effect on the system analysis is explained. Subsequently, sufficient conditions for solving state feedback gains and event-triggering parameters in terms of linear matrix inequalities are presented. Finally, numerical simulations are given to verify the effectiveness of the proposed method.